Selective transmission of multidrug resistant HIV to a newborn related to poor maternal adherence. Issue 5 (22nd October 2003) - Desai, N; Mathur, M
Abstract : Objectives: To report perinatal transmission of multidrug resistant (MDR) HIV related to variable maternal adherence antenatally. Methods: Case study including review of clinic records, adherence information, laboratory data, and HIV genotyping results in mother and infant. Results: Poor maternal adherence to clinic visits and antiretroviral therapy contributed to detectable viraemia antenatally. When tested for the first time at age 6 months, the infant was found to have virus with resistance to multiple drugs. In this case, prophylaxis with zidovudine (AZT) failed to prevent the transmission of the MDR strain. Conclusions: Perinatal transmission of MDR HIV can occur despite standard peripartum prophylaxis with AZT. Perinatal prophylaxis should be tailored to the mother's treatment history and resistance profile. Paediatric HIV specialists should be prepared to deal with a small, but slowly increasing number of babies with a "nightmare" multidrug resistant virus with limited treatment options.